Makna Di Balik Gerakan Literasi - Muhammad Mukaddar; Saidna Zulfiqar bin Tahir; M Chairul Basrun Umanailo; Darwin Abd Radjak; Andries Lionardo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study is to ascertain the meaning of the literacy movement in Buru district, where the movement's stated objective is to increase human resources. The issue is focused on the implementation process, which has been underway for three years but has yet to demonstrate the program's significance and impact on the community's real conditions. The approach taken in this study is qualitative, and the number of informants interviewed will be 15. These informants will be chosen purposefully, with the understanding that respondents will be considered related parties in order to accomplish the research objectives. The research was conducted in Namlea village, Buru district, with informants that included village officials, BPD members, representatives of community leaders, traditional leaders, and religious leaders, as well as community representatives with competencies relevant to the research objectives. This study collects data about the literacy movement's implementation through observation and in-depth interviews. In this research, I employ qualitative data analysis in accordance with Miles, Huberman, and Spradley's concepts. This study concludes that the program-based literacy movement has not yet fully grasped the meaning; people's awareness of literacy has focused on participation levels but not on activities that promote relaxation, protect the brain, prevent disease, and prolong life.